Artificial Intelligence in the work of I. Asimov I, Robot and the TV series Westworld - Kánský, Tomáš (Univerzita Pardubice, 2020)
This master's thesis aims to discover whether - and to what degree - are the fictional artificial beings, most of whom could be called robots, in the film I, Robot and the TV series Westworld beings that are conscious. To analyze the entities, Michio Kaku's levels of consciousness and Anil Seth's aspects of consciousness are used as a framework.
Obraz umělé inteligence v díle I. Asimova I, Robot a v sérii Westworld
Keywords: umělé vědomí; umělá inteligence; Westworld; Robot; Alex Proyas; Lisa Joy; Jonathan Nolan; science fiction; roboti; android; self; feedback loop; Anil Seth; Michio Kaku; artificial consciousness; artificial intelligence; Westworld; Robot; Alex Proyas; Lisa Joy; Jonathan Nolan; science fiction; robots; android; self; feedback loop; Anil Seth; Michio Kaku